Perlindungan Hak Anak dalam Perkawinan Siri Perspektif Hukum Keluarga Islam dan Undang-Undang Perlindungan Anak - Dody Wahono Suryo Alam (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
Unregistered (siri) marriages pose significant legal issues, particularly regarding the protection of children's rights born from such unions. This study aims to analyze the legal protection of children from siri marriages through the lens of Islamic Family Law and the Indonesian Child Protection Act. This qualitative research employs normative and empirical approaches, utilizing literature reviews and field observations at the Civil Registry Office in Jember. The findings reveal that children from siri marriages encounter challenges in obtaining legal identity, financial support, inheritance rights, and legal protection, despite the Constitutional Court Decision No. 46/PUU-VIII/2010 recognizing their civil relationship with their father. However, the implementation of this ruling remains hindered by administrative barriers and social stigma. Therefore, comprehensive efforts are needed, including legal reform, public education, and strengthening child protection institutions, to ensure the equitable fulfillment of children's rights in unregistered marriages.